2014
DOI: 10.1038/pr.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphisms and bronchopulmonary dysplasia

Abstract: Background: Vitamin D and its receptor (VDR) have important roles in perinatal lung development. The aim of this study was to investigate the relationship between VDR gene polymorphism and bronchopulmonary dysplasia (BPD) in preterm infants. Methods: VDR Fok I, Bsm I, Apa I, and Taq I polymorphisms were genotyped using restriction fragment length polymorphism in 109 preterm infants (47 with BPD, 62 without BPD). results: In univariate analysis, Ff (odds ratio (OR) = 3.937, P = 0.022, 95% confidence interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
0
14
1
1
Order By: Relevance
“…40 In a very recent study, VDR Fok 1 polymorphism was found to be associated with increased frequency of BPD. 41 Our study is the first in the literature to demonstrate a possible association between maternal/neonatal 25-OHD levels and BPD. We found that every 1 ng ml − 1 increase in vitamin D level of the mother and the newborn decreased the probability of BPD by 24% and 39%, respectively, showing that vitamin D level of the mother and the newborn was a significant predictor of BPD.…”
Section: Discussionmentioning
confidence: 59%
“…40 In a very recent study, VDR Fok 1 polymorphism was found to be associated with increased frequency of BPD. 41 Our study is the first in the literature to demonstrate a possible association between maternal/neonatal 25-OHD levels and BPD. We found that every 1 ng ml − 1 increase in vitamin D level of the mother and the newborn decreased the probability of BPD by 24% and 39%, respectively, showing that vitamin D level of the mother and the newborn was a significant predictor of BPD.…”
Section: Discussionmentioning
confidence: 59%
“…The other identified observational study (50) concluded that the VDR Fok I polymorphism was associated with an increased adjusted risk of BPD. However, the association was not detectable when controlling for the very important confounders, gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, genome-wide association studies have been variably successful [65, 66] and unsuccessful [67] in identifying candidate single nucleotide polymorphisms associated with BPD. Polymorphisms in the vitamin D receptor gene were recently shown to be associated with BPD in preterm newborns supporting preclinical studies in which vitamin D augments angiogenesis both in vitro and in LPS-induced experimental BPD [68, 69]. …”
Section: Introductionmentioning
confidence: 88%